EXERCISE STRESS TESTING : WHEN, HOW, AND WHAT IT MEANS? - Waskito, Budi Arief (Universitas Wijaya Kusuma Surabaya, 2012)
Exercise stress testing (EST) is a sensitive and informative examination of the cardiovascular response to exercise. Exercise is a common physiological stress used to elicit cardiovascular abnormalities not present at rest and to determine the adequacy of cardiac function. The electrocardiogram is the most common parameter used to evaluate the ischemic response during exercise. Exercise electrocardiography is one of the most frequent noninvasive modalities used to determine the likelihood and extent of coronary artery disease. The test is also used to estimate prognosis, to determine functional capacity, and to evaluate the effects of therapy. The indications, contraindications, protocol, when to terminate, interpretation of the result, and spesific clinical applications will be reviewed in this paper.